2018
DOI: 10.1175/jtech-d-17-0069.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Turbulence Intensity from CTD-Attached and Free-Fall Microstructure Profilers

Abstract: Turbulence intensity estimated from fast-response thermistors is compared between conductivitytemperature-depth (CTD)-attached and free-fall microstructure profilers, conducted at the same location within 2 h. The agreement is generally good but anomalously overestimated values, deviating from a lognormal distribution, appear sporadically in the CTD-attached method. These overestimated outliers are evident as spiky patches in the raw temperature gradient profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…The K ρ was also measured by using CTD-attached fast-response thermistors (AFPO7; Rockland Scientific International Company) (50, 51) on the KH-17-3 cruise for open water in the subarctic Pacific (SI Appendix, Table S2). Comparison study between these two measurement methods have been conducted at 100 stations in several cruises (51), including KH-09-4 (SI Appendix, Table S2) (51). Turbulence intensity estimated from CTD-fast-response thermistors was compared to those by free-fall microstructure profilers, conducted at the same location within 2 h, and the result was reported in Goto et al (51), where « is valid for 10 −10 < « <10 −8 W/kg after response correction (50) and data screening (51), and it has been confirmed that « from both measurement methods are comparable and within a factor of 3 (51).…”
Section: Methodsmentioning
confidence: 99%
“…The K ρ was also measured by using CTD-attached fast-response thermistors (AFPO7; Rockland Scientific International Company) (50, 51) on the KH-17-3 cruise for open water in the subarctic Pacific (SI Appendix, Table S2). Comparison study between these two measurement methods have been conducted at 100 stations in several cruises (51), including KH-09-4 (SI Appendix, Table S2) (51). Turbulence intensity estimated from CTD-fast-response thermistors was compared to those by free-fall microstructure profilers, conducted at the same location within 2 h, and the result was reported in Goto et al (51), where « is valid for 10 −10 < « <10 −8 W/kg after response correction (50) and data screening (51), and it has been confirmed that « from both measurement methods are comparable and within a factor of 3 (51).…”
Section: Methodsmentioning
confidence: 99%
“…To avoid measurement of artificial turbulence caused by the frames, the two fast-response thermistors (Fastip Probe model 07; henceforth FP07) were attached close to the bottom of the frames (Fig. 1 of the study 21 ). Probes whose spectra fit the universal spectrum better was used in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The data were retrieved from the Pacific Ocean (Fig. 1 ) 21 . They comprise profiles, each of which typically extends over a depth of 2000–6000 m below the sea surface, in turn comprising observational bins with width of .…”
Section: Methodsmentioning
confidence: 99%
“…They comprise profiles, each of which typically extends over a depth of 2000–6000 m below the sea surface, in turn comprising observational bins with width of . The turbulent energy dissipation rate for each bin, , is derived by averaging the observational values in the bin, which are estimated from the observed spectrum of the temperature vertical gradient based on the procedure presented in Goto et al 21 , 22 (see Supplementary Information A for the estimation procedure). We restrict our investigation to the intermittency occurring at larger scales, .…”
Section: Methodsmentioning
confidence: 99%